Making sense of Muslim fundamentalisms: the clash within Islam - Hurvitz, Nimrod (Routledge, Taylor and Francis Group, 2020)
Introduction -- Part I. Histories: 1. Moderate fundamentalists -- 2. Militant fundamentalists -- Part II. Mobilization: 3. Authority and leadership -- 4. The art and means of persuasion -- Part III. Moral order: 5. Images of the West -- 6. Culture wars -- 7. Women in the public sphere -- Concluding observations.